2006
DOI: 10.1002/icd.445
|View full text |Cite
|
Sign up to set email alerts
|

Changes in infant directed speech in the first six months

Abstract: The Mother-Infant Phonetic Interaction model (MIPhI) predicts that, compared with adult directed speech (ADS), in infant directed speech (IDS) vowels will be overspecified and consonants underspecified during the infants' first 6 months. In a longitudinal natural study, six mothers' ADS and IDS were recorded on 10 occasions during the first 6 months after their infants were born. Acoustic-phonetic measures, including the first two formant frequencies and duration for vowels and the duration of the fricative /s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
82
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 30 publications
5
82
0
1
Order By: Relevance
“…With technological advances, more studies are using high-density longitudinal corpora of mother-child speech (e.g. Brent and Siskind, 2001;Englund and Behne, 2006;Demuth et al, 2006;Soderstrom et al, 2008;Roy et al, 2009). Armed with an unprecedented amount of data enabled by the consortium of the child language data via the CHILDES database and new methodological approaches, this study revisits the old ''fine-tuning'' hypothesis and tests for any evidence of quantal changes in CDS around the time the child attains major linguistic milestones, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With technological advances, more studies are using high-density longitudinal corpora of mother-child speech (e.g. Brent and Siskind, 2001;Englund and Behne, 2006;Demuth et al, 2006;Soderstrom et al, 2008;Roy et al, 2009). Armed with an unprecedented amount of data enabled by the consortium of the child language data via the CHILDES database and new methodological approaches, this study revisits the old ''fine-tuning'' hypothesis and tests for any evidence of quantal changes in CDS around the time the child attains major linguistic milestones, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The driving forces behind the acoustic characteristics of this special register, variably referred to as motherese, baby talk, or infant-directed speech ͑IDS͒, have long been the object of speculation. Most researchers agree that caregivers adapt their speech in order to engage their children's attention and maintain positive rapport by enhancing the expression of emotion and affect ͑Fer-nald, 1989͑Fer-nald, , 1992Fernald and Simon, 1984;Kaplan et al, 1991;Stern et al, 1982;Uther et al, 2007͒. In addition, some researchers further hypothesize that IDS may also serve to facilitate language acquisition ͑Englund, 2005; Englund and Behne, 2006;Fernald, 2000;Liu et al, 2007;Sundberg, 2001;Werker et al, 2007͒. While the idea that caregivers may enhance linguistic categories when addressing their children is as old as the concept of IDS itself ͑see e.g., Ferguson, 1964͒, it was only recently that researchers turned to the acoustic signal as a possible level at which this enhancement may apply. This recent work indeed suggests that across-category acoustic distance is augmented in speech to infants when vowels and tones are measured ͑on vowels: Burnham et al, 2002;Kirchhoff and Schimmel, 2005;Kuhl et al, 1997; but see Englund and Behne, 2006;on tones: Liu et al, 2007on tones: Liu et al, , 2009; but see Kitamura et al, 2001;Papoušek and Hwang, 1991͒. In contrast, consonantal contrasts have received less attention, and the little work on them has reported conflicting results: some report enhancement ͑e.g., Malsheen, 1980;Sundberg, 2001͒, and others no difference or even deterioration ͑e.g., Baran et al, 1977;Sundberg and Lacerda, 1999͒. Given that consonants play a fundamental role in wordlearning and lexical access, both in childhood and later on ͑to give just a few examples, Cutler et al, 2000;Nazzi, 2005;New et al, 2008͒, it is important to assess the possibility that consonantal categories may be enhanced in speech addressed to young children.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have presented contradictory results on the degree of vowel space expansion in ID speech to populations both with and without hearing impairment (Cristia & Seidl, 2014;Englund & Behne, 2006;Kondaurova et al, 2012;C. Lam & Kitamura, 2010, 2012.…”
mentioning
confidence: 99%
“…Lam & Kitamura, 2010, 2012. Several studies have demonstrated no enhancement of the distance between vowel categories and/or expansion of the acoustic vowel space area in speech to children with normal hearing compared with AD speech (Cristia & Seidl, 2014;Englund & Behne, 2006). Although evidence of vowel space expansion exists when a talker is aware that an adult listener has a hearing impairment (Ferguson & Kewley-Port, 2002;Picheny, Durlach, & Braida, 1986), partial or no vowel space expansion was observed in speech to children with hearing impairment (Kondaurova et al, 2012;C.…”
mentioning
confidence: 99%